Online video- based resistance training improves the physical capacity of junior basketball athletes - Klusemann, M. J.; Pyne, D. B.; Fay, T. S.; Tristan, S.; Drinkwater, E. J. (The Journal of Strength and Conditioning Research, 2012)
Junior basketball athletes require a well-designed resistance training program to improve their physical development. Lack of expert supervision and resistance training in junior development pathways may be overcome by implementing an online video-based program. The aim of this study was to compare the magnitude of improvement (change) in physical performance and strength and functional movement patterns of junior basketball athletes using either a fully supervised or an online video-based resistance training program. Thirty-eight junior basketball athletes (males, n = 17; age, 14 ± 1 year; height, 1.79 ± 0.10 m; mass, 67 ± 12 kg; females, n = 21; age, 15 ± 1 year; height, 1.70 ± 0.07 m; mass, 62 ± 8 kg) were randomly assigned into a supervised resistance training group (SG, n = 13), video training group (VG, n = 13) or control group (CG, n = 12) and participated in a 6-week controlled experimental trial. Pre- and posttesting included measures of physical performance (20-m sprint, step-in vertical jump, agility, sit and reach, line drill, and Yo-Yo intermittent recovery level 1), strength (15 s push-up and pull-up), and functional movement screening (FMS). Both SG and VG achieved 3-5% ± 2-4% (mean ± 90% confidence limits) greater improvements in several physical performance measures (vertical jump height, 20-m sprint time, and Yo-Yo endurance performance) and a 28 ± 21% greater improvement in push-up strength compared with the CG. The SG attained substantially larger gains in FMS scores over both the VG (12 ± 10%) and CG (13 ± 8%). Video-based training appears to be a viable option to improve physical performance and strength in junior basketball athletes. Qualified supervision is recommended to improve functional movement patterns in junior athletes.